Optimization of production batches in a circular supply chain under uncertainty. Issue 10 (2022) - Morjéne, Yasmine; Ndhaief, Nadia; Rezg, Nidhal
Abstract: During the covid-19 outbreak, millions of people are required to use disposable masks to protect themselves from this infectious disease. Under an exponential spread tendency of this pandemic, the conventional end of life of these plastic products is to dispose of them in landfills or to incinerate them. Actually, this scenario is the most optimistic one since millions of tonnes of masks are ended up in oceans. Therefore, recycling which is one of the circular economy concepts remains the key solution aiding countries to mitigate masks pollution, in addition to its role in decreasing the widespread of the disease. In this paper, we will exanimate several studies dealing with reverse logistics and circular economy, then we will develop a closed-loop supply chain design during the pandemic and translate it mathematically as a MILP model under certain and uncertain client demand. Finally, the problem will be solved using IBM ILOG Cplex Optimization Studio and the obtained results will be discussed.